Effect of the Flipped Classroom Model with Loop Game on Learning Outcomes in Economics Threshold Concepts - Jimoh, Akinola Saliu; Mohammed, Abidat Oluwashola; Lawal-Arogundade, Samod Olayiwole; Obimuyiwa, Gabriel Ayodeji (Asian Journal of Assessment in Teaching and Learning, 2024)
This study investigated the influence of implementing a Flipped Classroom model integrated with Loop Game activities on students’ learning outcomes in Economics Threshold Concepts. The study employs a quasi-experimental design with a one-group pre-test and post-test format. A systematic sampling technique was used to select a sample of 12 schools from the four zones in Lagos State Education District V, using three schools from each zone. Intact classes of year two senior secondary school students were used in each sampled school. The study raised two research questions and tested one hypothesis at a 0.05 level of significance. Results indicated that the application of the Flipped Classroom model combined with Loop Game activities significantly improves learning outcomes in Economics Threshold Concepts. The pre-test average score was observed to be 5.22, which increased to 7.42 in the post-test, amounting to over 40% increase. This descriptive comparison illustrated a substantial enhancement in students’ understanding of the material following the implementation of this learning model. A paired sample t-test analysis confirmed a significant increase in learning outcomes (r = 0.81, p < 0.05). These findings demonstrated that the use of the Flipped Classroom model with Loop Game activities effectively enhances learning outcomes in Economics Threshold Concepts. It was recommended, therefore, that senior secondary schools should make efforts to integrate the Flipped Classroom model with Loop Game activities in teaching Economics Threshold Concepts as it has been found to create more effective and interactive learning experiences for senior secondary school students.